Empowering women and communities to promote universal health coverage in rural Zambia. Issue 8 (17th November 2018) - Quigley, Paula; Green, Cathy; Soyoola, Miniratu; Kureya, Tendayi; Barber, Caroline; Mubuyaeta, Kenneth
ABSTRACT: From 2014 to 2016, we supported the national Safe Motherhood Action Group initiative in five rural districts of Zambia. An empowerment approach mobilised communities and built local capacity to take action in support of improved access to maternal and newborn health. The endline survey and a range of qualitative reviews showed significant differences in intervention communities in antenatal care attendance, skilled birth attendance, use of modern family planning and knowledge of maternal danger signs. This comprehensive approach has the potential to reduce inequity and help achieve universal health coverage in addition to other wide-reaching societal benefits at a modest cost.